KINERJA PEMERINTAH KOTA PADANG DALAM PENANGGULANGAN BANJIR DAN BENCANA GALODO DI SUMATERA BARAT (STUDI PADA PENANGANAN PASCABENCANA) - Miftahul Hasanah; Nabila Laila Rani; Rifha Tri Oktary; Boni Saputra (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to assess the performance of the Padang City Government, through the Regional Disaster Management Agency (BPBD), in addressing flooding and Galodo disasters, particularly in the post-disaster phase. A qualitative descriptive approach was employed, relying on literature studies and interviews. The findings indicate that the BPBD plays a crucial role in aid distribution, rehabilitation, and economic and social recovery. While its performance is quite responsive, it still faces challenges related to resources, budget, and intersectoral collaboration. Disaster management remains largely reactive. Therefore, institutional capacity building and improved coordination are needed to achieve more preventative and sustainable management.